The DESIGNING READING APPLICATIONS (R-APPS) FOR SENIOR HIGH SCHOOL: English - BAHTIAR, YUYUN (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2021)
The main objective of this research is to explore the result of the use of R-Aps as a new tool which helps increasing students’ motivation in 11th Grade. The study is based on a situation where students have to do learning at home, then a reading application is developed for students to have an increase in learning motivation. The sample of the students’ population for this study is all of 11th in MA Mambaul Ulum Megaluh Jombang. The instruments used in this study were 1) Validation sheet by Validator Expert 2) teacher interview 3) a questionnaire of the students’ responses. From the calculation of the above-average obtained results of 3.97 which belonged to the category of good so that could be concluded that the use of learning media R-Apps is effective. And Regarding the data analysis, mean, percentage, and total score. The result indicated that 1) the students’ English reading comprehension ability increased significantly after learning with reading application 2) Reading Application is worthy as a new tool to increase student motivation 3) the results of the study showed that the media obtained good criteria with a score of 3.97 on the Linkert scale which showed that the media was feasible to be implemented in the classroom.